2019
DOI: 10.1002/acr.23861
|View full text |Cite
|
Sign up to set email alerts
|

Increased Morbidity and Mortality of Scleroderma in African Americans Compared to Non–African Americans

Abstract: Objective. African Americans with scleroderma have more severe disease and higher mortality than non-African Americans. Differences in rates of diffuse disease, autoantibody status, or socioeconomic status have not completely explained this phenomenon. Our study evaluates these risks at our site.Methods. A retrospective study comparing African American and non-African American patients with scleroderma seen from 2008 to 2016 was performed. Groups were matched by sex, age at first visit, date of first visit, di… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

8
37
1

Year Published

2019
2019
2023
2023

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 43 publications
(49 citation statements)
references
References 25 publications
8
37
1
Order By: Relevance
“…African Americans, for example, are known to have a higher incidence of SSc, an earlier age of onset, and a greater frequency of interstitial lung disease (ILD) and pulmonary hypertension (PH) compared to white SSc patients [4,5,[7][8][9]. Data on black SSc patients however mostly stem from African Americans and figures may be influenced by environmental and socioeconomic factors and access to health care [10,11]. Differences in the autoantibody profile have also been reported between races; anticentromere antibodies (ACA) for example are frequent in Caucasian patients, whereas anti-topoisomerase-I antibodies (ATA) are highly prevalent in Choctaw Native Americans, Thais and African Americans [1,3,12,13].…”
Section: Introductionmentioning
confidence: 99%
“…African Americans, for example, are known to have a higher incidence of SSc, an earlier age of onset, and a greater frequency of interstitial lung disease (ILD) and pulmonary hypertension (PH) compared to white SSc patients [4,5,[7][8][9]. Data on black SSc patients however mostly stem from African Americans and figures may be influenced by environmental and socioeconomic factors and access to health care [10,11]. Differences in the autoantibody profile have also been reported between races; anticentromere antibodies (ACA) for example are frequent in Caucasian patients, whereas anti-topoisomerase-I antibodies (ATA) are highly prevalent in Choctaw Native Americans, Thais and African Americans [1,3,12,13].…”
Section: Introductionmentioning
confidence: 99%
“…[13][14][15] Similarly, African American patients with SSc-ILD may also exhibit more severe ILD. [16][17][18] However, a recent analysis demonstrated that after adjustment for socioeconomic factors, African American race was not a significant risk factor for mortality in a relatively large cohort of SSc patients (N = 402) 18 Among SSc-ILD patients who participated in SLS I and II, there was no difference in the course of the FVC% predicted, nor long-term survival, between African American and non-African American participants, even after adjustment for baseline disease severity. 19 These findings suggest that confounding factors should be considered when interpreting the results of observational studies where patients have varying access to care, treatment, and follow-up.…”
Section: Demographic Factorsmentioning
confidence: 99%
“…Overall, and in the context of these published reports that underscore the disproportionate and adverse impact of scleroderma among African Americans, and in light of the ongoing efforts of the GRASP study, the current article by Moore et al emphasizes the importance of socioeconomic status and of socioeconomic determinants of health, to account for differences in clinically relevant outcomes . These reports emphasize to the reader, each in its own way, the value of an optimal study design, which can concomitantly examine the independent contribution of socioeconomic status, and of clinical, serologic, and genetic determinants to outcomes of interest in scleroderma.…”
mentioning
confidence: 93%
“…In addition, the mean age at death was younger among the African American patients. Many years later, directly related to the study by Moore et al in this issue of Arthritis Care & Research , the question remains: why are African Americans disproportionately affected with greater morbidity and excess mortality once diagnosed with scleroderma?…”
mentioning
confidence: 99%
See 1 more Smart Citation